Histological evaluation of the response of apical tissues to glass ionomer and zinc oxide eugenol based sealers in dog teeth after root canal treatment - Leonardo, M. R.; Almeida, W. A.; da Silva, LAB; Utrilla, L. S. (Munksgaard Int Publ Ltd, 1998)
The object of the study was to compare two commercial root canal sealers: Ketac-Endo (a glass ionomer cement) and Fill Canal (a zinc oxide-eugenol cement). A total of 34 root canals from dog premolars with vital pulps were used. After instrumentation, the root canals were sealed with Ketac-Endo and Fill Canal cements using gutta-percha and a lateral condensation technique. After 270 days the animals were sacrificed with an anesthetic overdose and the maxillae and mandibles were removed and fixed in formalin for 48 h. After routine histological processing the sections were stained with hematoxylin-eosin and Mallory trichrome stains. Microscopic analysis revealed that Ketac-Endo cement presented better results than Fill Canal cement.
Keywords: glass ionomer cement; root canal sealer; root canal treatment; zinc oxide-eugenol cement